2021
DOI: 10.3389/fenvs.2021.765696
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physico-Chemical Properties Change Across an Urbanity Gradient in Berlin

Abstract: In this study the impacts of urbanity on physical soil properties were explored by measuring water stable aggregates, combined particle size, infiltration rate and hydrophobicity across an urban gradient. The use of a gradient allowed for the relative importance of different environmental drivers to be assessed. We sampled 54 sites across Berlin and used a pre-existing database of environmental variables to extract three main axes of variation relating to urbanity, soil nutrient content, and heavy metal conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Our study provides evidence that we cannot solely rely on soil chemistry research to explain plant-fungal interactions in urban systems. Previous research from the same study system has suggested that urban soils have lower levels of aggregate stability (Whitehead et al, 2021), our current study suggests that a lack of AM fungi, previously described as key causal agents in aggregate formation (Lehmann et al, 2020), is likely not the leading cause of the reduction in aggregate stability in this system.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our study provides evidence that we cannot solely rely on soil chemistry research to explain plant-fungal interactions in urban systems. Previous research from the same study system has suggested that urban soils have lower levels of aggregate stability (Whitehead et al, 2021), our current study suggests that a lack of AM fungi, previously described as key causal agents in aggregate formation (Lehmann et al, 2020), is likely not the leading cause of the reduction in aggregate stability in this system.…”
Section: Discussionsupporting
confidence: 56%
“…However, the basis of all plant, and consequently animal, diversity is the soil. Urban soils have variously been described as compressed (Yang and Zhang, 2011), polluted (Hanfi et al, 2020) and lacking aggregates (Whitehead et al, 2021), expressing increased pH (Asabere et al, 2018) and salinity (Dmuchowski et al, 2021). As such, the ability of symbiotic fungi to buffer the negative impacts of urbanity upon plant hosts makes them a vital component of maintaining urban greenspaces.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research from the same study system as that of this study has observed a change in soil physico-chemical properties in response to an "urban syndrome" of variables (Whitehead et al, 2021). These changes included a reduction in aggregate stability and an increase in water infiltration rate.…”
mentioning
confidence: 63%
“…Soil hydrophobicity causes soil water repellency, which determines the infiltration of water into the soil, this controls precipitation and contribute to surface run-off or flooding [36]. Large-particle soils increase the levels of hydrophobicity [37]. The structure of the studied area as shown in Table 1 is loam-sandy in structure; this implies that it can have high hydrophobicity.…”
Section: Soil Structurementioning
confidence: 99%